Persuasive design-related motivators, ability factors and prompts in early childhood apps: A content analysis. (February 2023) - Mallawaarachchi, Sumudu R.; Tieppo, Andria; Hooley, Merrilyn; Horwood, Sharon
Abstract: Despite the increasing rates of early childhood smartphone and tablet use and the possible link to engagement-promoting persuasive digital environment design, there has been limited research examining persuasive design features in early childhood apps. The current content analysis aimed to systematically evaluate the prevalence of persuasive design features within popular early childhood apps. Comparisons in persuasive design features between free and paid apps, as well as 'Teacher-Approved' and other apps were also examined. A coding scheme, guided by the Fogg behavioral model (2009), was applied to 132 apps. Each persuasive feature belonged to either of the three main components; motivation, ability or prompts, and was dichotomously coded to indicate whether it was present. Of the 132 apps analyzed, a high prevalence of passive motivation features (vibrant colors and music), and ability features (in-game help suggestions and repetitive tasks) were noted across a majority of apps. Further, prompts were more prevalent in free apps compared to paid apps, while there were no differences between free and paid apps in other features. Teacher-Approved apps contained less advertising and fear-based motivation features compared to non-approved apps. These results outline the need to consider the developmental implications of persuasive design features in apps and to examine how they may contribute to problematic screen behaviors in early childhood. Highlights: Persuasive design in apps attempt to motivate, facilitate ability and prompt child users. Vibrant colors and sounds, in-game help and repetitive tasks are highly prevalent in apps. Free apps contain more commercial prompts than paid apps. Teacher-Approved apps contain less advertising and fear-based motivators than other apps. More work is needed on how persuasive features may interact with child development.